CLINICAL EFFICACY OF MONOTHERAPY WITH INDAPAMIDE IN PATIENTS WITH ARTERIAL HYPERTENSION OF THE I-II DEGREES - E. Yu. Тourkassova; T. G. Volkova; E. M. Idrissova; E. M. Vorobyeva; R. S. Karpov (Рациональная фармакотерапия в кардиологии)
Aim. To assess antihypertensive efficacy of monotherapy with indapamide (Akripamide, Akrihin, Russia) and its influence on blood levels of carbohydrates, lipids and electrolytes in patients with essential hypertension (EH). Methods. 30 patients with EH I-II degrees were treated with indapamide 2,5 mg daily during 3 months. Ambulatory blood pressure (BP) monitoring was made before and after the treatment as well as blood levels of carbohydrates, lipids and electrolytes were assessed. Results. 3-month indapamide monotherapy resulted in achievement of BP target levels in 76.6% of patients. Significant decrease in daily , day-time and nighttime BP , BP burden and daytime BP variability were observed. Number of patients with insufficient night decrease of systolic and diastolic BP was significantly decreased. No negative influence of indapamide on blood levels of lipids and electrolytes was observed. Conclusion. Indapamide is effective antihypertensive drug with satisfactory tolerance.